Poetic force poetry after Kant - McLaughlin, Kevin 1959- (Stanford Univ. Press, 2014)
Ur-ability : force and image from Kant to Benjamin -- Hölderlin's peace -- Poetic reason of state : Baudelaire and the multitudes -- Arnold's resignation -- Epilogue : making room for reason
Includes bibliographical references and index
Keywords: Kant, Immanuel 1724-1804 / Influence / Kant, Immanuel 1724-1804 / 1800 - 1999; Kant, Immanuel -- 1724-1804; Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1800-2000; Poetry / History and criticism / 19th century; Aesthetics, Modern / 20th century; Philosophy, Modern / 20th century; Aesthetics, Modern; Influence (Literary, artistic, etc.); Philosophy, Modern; Poetry / Criticism, interpretation, etc; Rezeption; Ästhetik; Literaturtheorie